PERBEDAAN PENGGUNAAN MODEL DISCOVERY LEARNING DAN METODE CERAMAH TERHADAP HASIL BELAJAR PENGETAHUAN IPA SISWA - Sari, Nurhayati Nilam; Zuryanty, Zuryanty; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the reality in the field that students still consider science learning as difficult learning and become a scourge for them. There are still many students who are not interested in science learning because learning is taught in a monotonous way and only holds on textbooks. Dominant students still receive learning from the teacher instead of finding their own concepts according to the nature of science learning. This study aims to determine Differences Of The Use Of Discovery Learning Models And Lecture Method On Student Learning Outcomes Of Students On Theme 1 at 4th Grade Of Elementary School III Group In The Ampek Angkek Subdistrict Agam DistrictThis research is a quantitative research with quasi type of experimental design, Two Group posttest-only design design. The population in this study were all class IV in Elementary School III in Ampek Angkek Subdistrict. Sampling is done by probability sampling technique with simple random sampling type. Data collection instruments used in the form of objective questions test. Data analysis used descriptive statistics and t test.Based on the results of the study obtained t count > t table where t count = 5,35 > t table = 1.72 means that Ha is accepted and Ho is rejected. The average learning outcomes of the Discovery Learning model class are 83,8 higher and the average learning outcomes of the lecture method class is 61,4. This shows that there is a significant difference between the Discovery Learning model class and the lecture method, where the learning outcomes of groups that use the Discovery Learning model are better than those that use the lecture method. Keyword: Discovery Learning model, lecture method, learning outcomes, science